Perceptions of provincial and district level managers' on the policy implementation of school oral health in South Africa - Mpho Molete; Aimee Stewart; Aneesa Moolla; Jude Ofuzinim Igumbor (BMC, 2021)
Abstract Background Although school oral health programmes have been ongoing for years, there is little evidence to show how their policy elements are governed or translated into tangible implementation activities and population outcomes at the district level. The need for such a study is heightened by the persistent burden of oral health conditions and unmet oral treatment needs of South Africa's children. This study therefore sought to describe provincial and district level managers' perceptions of school oral health policy, and to identify gaps and conditions needed for successful policy implementation. Methods This was an exploratory qualitative study where eight oral health managers from the Gauteng provincial and district offices were purposively sampled. Data were collected using interviews and a policy review rubric. The 10 Siddiqi governance principles framework was used to guide the data analysis. Results The managers' perceptions and the policy document review indicated that national policy covered the principles of strategic vision, responsiveness to health needs, equity and inclusivity with clarity; however these principles were not translated consistently by the managers at a local level. Policy gaps were identified in the areas of stakeholder involvement, accountability, reliable information systems and ethical guidelines. Much of the gaps in policy translation were attributed to inadequate human resources and poor communication processes by the national leadership to support district level implementation. Conclusions There were inconsistencies in policy awareness and translation in the districts and hence an in-depth review of the policy translation gaps is paramount to its efficient resolution in the context of resource and capacity limitations. Furthermore, optimizing multi-sectoral participation and identifying shared, novel and practical solutions to policy translation impediments is necessary.